2022
DOI: 10.1111/cdoe.12765
|View full text |Cite
|
Sign up to set email alerts
|

Influence of two caries detection strategies on the quality of life of preschool children: An analysis of secondary outcomes of a 2‐Year randomized clinical trial

Abstract: ObjectiveThis randomized clinical trial aimed to evaluate the influence of two caries diagnosis strategies, and subsequent management, on oral health‐related quality of life (OHRQoL) of preschoolers. Additionally, the association of the OHRQoL outcomes with the clinician‐centred primary outcome used in the main study was also explored.Materials and MethodsThis study refers to the OHRQoL secondary outcomes analyses of the so‐called RCT ‘CARDEC‐1’. Three‐ to 6‐year‐old children were randomly allocated in two car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(106 reference statements)
0
1
0
1
Order By: Relevance
“…However, this type of outcome has rarely been used as primary outcome in dentistry 22 . It was recently found that changes in children's oral health‐related quality of life (by parental proxy) was related to the primary endpoint, a clinically centred measure (number of new operative interventions during the follow‐up) 23 . Findings such as this may indicate that PROMs in RCTs for dental caries should be considered as surrogates in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, this type of outcome has rarely been used as primary outcome in dentistry 22 . It was recently found that changes in children's oral health‐related quality of life (by parental proxy) was related to the primary endpoint, a clinically centred measure (number of new operative interventions during the follow‐up) 23 . Findings such as this may indicate that PROMs in RCTs for dental caries should be considered as surrogates in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso o instrumento é composto por 13 questões, divididas em uma seção de impacto infantil (sintomas da criança, função, domínios psicológicos e de autoimagem/interação social) e uma seção de impacto familiar (domínios de sofrimento parental e função familiar). ECOHIS também demonstrou ser responsivo ao tratamento odontológico e refletir o comprometimento da saúde bucal, onde escores mais altos indicam um maior impacto negativo dos problemas de saúde bucal na QVRSB das crianças e suas famílias (3,31).…”
Section: Introductionunclassified